2021
DOI: 10.47836/ifrj.28.1.07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of roasting conditions on anthocyanin, total phenolic content, and antioxidant capacity in pigmented and non-pigmented rice varieties

Abstract: Roasting has been suggested to enhance the nutritional quality of many foods. The present work determined how roasting temperature (100, 150, and 200°C) and duration (10 and 20 min) affect anthocyanin, total phenolic contents, and antioxidant capacity in pigmented and non-pigmented rice. The concentration of anthocyanin in pigmented rice increased by 15% when roasted at 100°C for 20 min, but it dramatically decreased at higher temperature for longer time. The anthocyanin analysis profile showed that cyanidin-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Roasting alters the composition of bioactive compounds in the barnyard millet and consequently. This will affect the antioxidant properties of the sample (28).…”
Section: Dpph Free Radical Scavencing Activitymentioning
confidence: 99%
“…Roasting alters the composition of bioactive compounds in the barnyard millet and consequently. This will affect the antioxidant properties of the sample (28).…”
Section: Dpph Free Radical Scavencing Activitymentioning
confidence: 99%
“…According to the Indonesian Food and Drug Supervisory Agency's guidelines, a maximum of 4% is allowed because ash contains minerals that might produce precipitate in the kidneys, posing a health risk. The ash concentration in rice bran reflects the mineral richness of the rice bran (Yamuangmorn et al, 2021). Due to the semidry physical structure of rice, Sirampog black rice has a low ash concentration.…”
Section: Ashmentioning
confidence: 99%
“…Pigmented or black rice is a plant known for its high antioxidant content [4], and "Sembada Hitam" is a cultivar of rice that belongs to the Poaceae family [8]. Studies have shown that black rice has six times higher antioxidant levels than white rice [9]. Cyanidin-3-glucoside, peonidin-3glucoside, malvidin-3-glucoside, peonidin-3-glucoside, petunidin-3-glucoside, myricetin-7-O-glucoside, and other cyanidin metabolites are among the antioxidants found in black rice [10].…”
Section: Introductionmentioning
confidence: 99%